The efficiency of the interim relief institution by suspending an individual or regulatory act (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article analyses the provisions of the Administrative Procedure Code of Ukraine on interim relief through suspension of a regulatory legal act and examines the Supreme Court’s case law with regard to the efficiency of application of this administrative procedure institution. In fulfilling the main tasks of administrative proceedings, the institution of interim relief is of great importance, as it allows the plaintiff to protect his or her rights and interests at the stage of applying to an administrative court by suspending the effect of an unlawful decision of a public authority. In the course of the court practice study, a gap in the current legislation and law enforcement practice has been identified, namely: when an interim relief order is cancelled by an appellate court, the authority believes that during the time its decision was suspended, such a legal act gives rise to rights and obligations for the parties. However, such a position of the authority is inconsistent with the provisions of the Constitution of Ukraine and the decision of the Constitutional Court of Ukraine, but is applied by the Supreme Court. To address this problem, it has been proposed to amend the Code of Administrative Procedure of Ukraine to provide that appellate and cassation courts, when issuing a decision to set aside a ruling on interim relief by suspending the effect of a regulatory act, should determine that the court ruling loses legal force from the date of the court's decision. In this case, the legislation should clearly state that during the time when the court of first instance ruling was in force, the effect of the legal act was suspended and did not give rise to any rights and obligations for the parties to the litigation, and in case the court ruling on interim relief is cancelled, the effect of the legal act does not have retroactive effect. The institution of interim relief should be effective and protect the violated rights of individuals.